2012
DOI: 10.1590/s0102-67202012000300006
|View full text |Cite
|
Sign up to set email alerts
|

Ressecção laparoscópica dos cistoadenomas pancreáticos

Abstract: -Background -Laparoscopic pancreatic resections have become increasingly frequent with good results reported by several centers. However, few studies have focused on laparoscopic treatment of pancreatic cystic lesions. Aim -To analyze the results of minimally invasive treatment of pancreatic cystic lesions. Methods -Were included all laparoscopic pancreatic resections performed at three centers. Surgical procedures included resection of the pancreas and left enucleations (with or without splenectomy). The post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In Brazil, at our knowledge, this is the first comparative study between the two laparoscopic distal pancreatectomy techniques with and without spleen preservation, according to the splenic vessel preservation technique. As Farah et al 9 as Machado et al 13 described a case series of laparoscopic distal pancreatic procedures with spleen preservation; however, they did not specify the technique or the specific results from this group. In the present study, similarities between the two methods were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, at our knowledge, this is the first comparative study between the two laparoscopic distal pancreatectomy techniques with and without spleen preservation, according to the splenic vessel preservation technique. As Farah et al 9 as Machado et al 13 described a case series of laparoscopic distal pancreatic procedures with spleen preservation; however, they did not specify the technique or the specific results from this group. In the present study, similarities between the two methods were observed.…”
Section: Discussionmentioning
confidence: 99%